Influence of School Environment on Effective Teaching of English Language in Katsina State, Nigeria - Nuraddeen Adamu Kanon-Haki; Karima Abdulkarim; Sule Muhammad (Penerbit Hellow Pustaka, 2026)
The effectiveness of English Language teaching in Nigerian secondary schools is influenced not only by teacher competence but also by the school environment and availability of instructional materials. This study examined the influence of school physical environment and instructional resources on effective English Language instruction in secondary schools in Katsina State, Nigeria. Employing a descriptive correlational research design, the study involved a population of 2,556 English Language teachers across 255 public secondary schools, from which a sample of 333 teachers was selected using the Research Advisors (2006) table. Data were collected through a structured questionnaire and analyzed using descriptive statistics, including mean and standard deviation, and multiple regression analysis to determine the relationships between variables. Findings revealed that the school physical environment, including classroom space, ventilation, lighting, cleanliness, and overall school facilities, significantly enhances teachers’ instructional effectiveness and students’ engagement. Similarly, the availability of instructional materials such as textbooks, charts, audio-visual aids, and up-to-date teaching resources was found to positively influence lesson delivery and interactive teaching. Multiple regression analysis confirmed that both the physical environment (β = 0.412, p = 0.000) and instructional materials (β = 0.389, p = 0.000) significantly predict effective English Language teaching. These findings underscore the critical role of adequate school infrastructure and instructional resources in improving teaching outcomes. The study recommends that policymakers, school administrators, and community stakeholders prioritize the provision and maintenance of conducive learning environments and sufficient instructional materials to enhance the quality of English Language education in Katsina State.